Corporate Boards Gender Diversity and Earnings Persistence: The Case of French Listed Firms (Global Journal of Management and Business Research, 2012)
This article empirically tests the impact of gender diversity of the boards of directors on earnings quality in general, and on earnings persistence in particular. Using a sample of 70 French firms listed at the SBF 120 index, we find that the enhancement of earnings persistence could not attributed to gender diversity. The results do not display significant differences among firms with female and male directors. Those results may be traced back to the sociopsychological attitude adopted by female directors, and by the visibility of barriers that would hinder their hierarchical progression.
Keywords: diversity; gender; board of directors; earnings persistence; SBF120